2003
DOI: 10.1055/s-0037-1613389
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-based biomaterials to deliver human growth factors

Abstract: SummaryFibrin-based biomaterial preparations can be used as provisional growth matrices for cells important in tissue repair during wound healing in vivo. Their efficacy can be enhanced by including bioactive agents that promote specific cellular responses. This study examined the controlled delivery of the angiogenic growth factors bFGF, VEGF165, and VEGF121 using biomatrix preparations prepared from Fibrin Sealant product components. The growth factors were added prior to formation of the Fibrin Sealant clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 39 publications
4
146
1
Order By: Relevance
“…One possibility is the use of other angiogenic growth factors (Richardson et al, 2001;Wong et al, 2003). So, in addition to FGF-2, we individually tested platelet derived growth factor-BB (PDGF-BB), vascular endothelial growth factor (VEGF 165 ), and bone morphogenic protein-2 (BMP-2) at 1, 10, and 100 ng/mL, while keeping all other construct components constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is the use of other angiogenic growth factors (Richardson et al, 2001;Wong et al, 2003). So, in addition to FGF-2, we individually tested platelet derived growth factor-BB (PDGF-BB), vascular endothelial growth factor (VEGF 165 ), and bone morphogenic protein-2 (BMP-2) at 1, 10, and 100 ng/mL, while keeping all other construct components constant.…”
Section: Resultsmentioning
confidence: 99%
“…The chorioallantoic membrane (CAM) assay, used for more than half a century, has become a mainstay in the study of blood vessel development (Auerbach et al, 2003;Cruz et al, 2000;Cruz et al, 1997;DeFouw and DeFouw, 2000a;DeFouw and DeFouw, 2000b;Djonov et al, 2000a;Djonov et al, 2000b;McDonnell et al, 2005;Rizzo and DeFouw, 1996;Rizzo et al, 1995;Rizzo et al, 1993). The CAM assay has also proved useful for biological devices and in tissue engineering applications, particularly those concerning biocompatibility studies and angiogenic responses to tissue-engineered constructs (Borges et al, 2003a;Borges et al, 2003b;Nguyen et al, 1994;Ribatti et al, 2001;Rickert et al, 2003;Valdes et al, 2003;Valdes et al, 2002;Wong et al, 2003). In this work we extend the CAM assay in the development of a histological technique to specifically examine direct vascular invasion into fibrin-based constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen peptides have also been used, with preclinical data demonstrating increased collagen synthesis [129], maintenance of homeostasis [130] and improved healing, as judged by mean average diameter, distribution of fibrils and GAG composition [131]. The utilisation of fibrin has been advocated based on its high cytocompatibility, biodegradability, controllable cross-linking, carrier capacity and presence of several ECM proteins, such as fibronectin, that enhance cell adhesion and proliferation [132][133][134]. Preclinical analysis revealed that fibrin glue around the suture site enabled rabbit flexor tendon healing with smooth gliding surface and without formation of adhesions [119].…”
Section: Minimally Invasive Strategies For Small Tendon Injuriesmentioning
confidence: 99%
“…Fibrin glue enjoys widespread clinical application as a wound sealant, a reservoir to deliver growth factors and as an aid in the placement and securement of biological implants (Vasita et al 2006, Inman et al 2003, Pandit et al 2000, DeBlois et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…In the cellular environment, fibrin specifically binds to a variety of proteins, including fibronectin, albumin, FGF2, VEGF, and IL-1 (Fakhry et al 2005). These properties make it an interesting drug and cell delivery system for various applications in tissue engineering (Vasita et al 2006, Inman et al 2003, Pandit et al 2000, DeBlois et al 1994, Rai et al 2005. Previous studies have focused on capabilities with respect to tailoring the scaffold to generate release profiles of the growth factors over time.…”
Section: Introductionmentioning
confidence: 99%